2007
DOI: 10.1111/j.1470-6431.2006.00578.x
|View full text |Cite
|
Sign up to set email alerts
|

Missed opportunities? Reaching the ethnic consumer market

Abstract: Changing population demographics within the UK have become a source of increased interest to marketers as companies have realized the importance of targeting their products and advertising efforts towards minority and ethnic groups. In addition, as the UK’s ethnic minorities grow in both numbers and in terms of prosperity, so does the commercial significance of this market. A clearer understanding of both the nature of changing markets and the relative importance of different minority ethnic groups as consumer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 11 publications
(34 reference statements)
1
27
0
Order By: Relevance
“…A growing number of marketers are interested in targeting ethnic consumers in the UK and across Europe given the current demographics shifts and rise in cultural diversity (Chaudhry and Crick, 2004;Emslie et al, 2007;Jamal, 2003). Previous research has found ethnicity to have a significant impact on consumption patterns, media usages and ethnic response to marketing efforts (Donthu and Cherian, 1994;Hui et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of marketers are interested in targeting ethnic consumers in the UK and across Europe given the current demographics shifts and rise in cultural diversity (Chaudhry and Crick, 2004;Emslie et al, 2007;Jamal, 2003). Previous research has found ethnicity to have a significant impact on consumption patterns, media usages and ethnic response to marketing efforts (Donthu and Cherian, 1994;Hui et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of shortcomings in the existing literature can be identified. First, and to the best of our knowledge, no previous research has specifically explored ethnic consumers' responses to sales promotional activities in the UK, where ethnic minority population represents the fastest growing segment of the total population (Jamal, 2005) and is expected to account for 10% of the UK population by 2020 (Emslie et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The vendors in the street market understand how to sell products to target customers, how to emphasize commonality with the mainstream markets and where the differences lie ( Emslie et al , 2007 ). Over the past several years, working consumers of 21 -54 years of age in large growing cities like Mexico have shown tendency to shop for local food in multinational self-service stores as they perceive these outlets as a place of convenience and prestige to purchase ethnic food (for example Cooper and Nelson, 2003 ).…”
Section: Socio-cultural Determinants and Ethnicitymentioning
confidence: 99%
“…These markets reveal the relative importance of traditional and ethnic values of consumers and facilitate both consumer understanding and market development. Street market vendors understand how to sell products to target customers and Downloaded by [National Sun Yat-Sen University] at 11:10 03 January 2015 how to emphasize commonality with the mainstream markets and where the differences lie (Emslie, Bent, & Seaman, 2007). Over the past several years working consumers between 21-54 years in large growing cities such as those in Mexico have shown tendencies to shop locally for food in multinational selfservice stores as they perceived these outlets as a place of convenience and prestige to purchase ethnic food (e.g., Cooper & Nelson, 2003).…”
Section: Review Of Literature and Hypotheses Framework Sociocultural mentioning
confidence: 99%